La personne déclarée morte par l’appelant au service téléphonique d’urgence : une source de désalignement interactionnel - Marty Laforest; Jessica Rioux-Turcotte (Communiquer)
This article focuses on emergency calls. Drawing on research in the field of talk-in-interaction, it explores how reporting death often leads to communication difficulties between caller and call taker. The study is based on an investigation of a corpus of calls made to 9-1-1 emergency service. It describes the caller’s resistance to the call taker’s requests and instructions in this situation. This interactional misalignment is associated with the standardized call processing procedures taught to call takers. It is argued, in conclusion, that integrating basic elements of talk-in-interaction analysis into the call taker’s training would lead to improved cooperation from the caller in all circumstances.